Traction alopecia: the root of the problem - Billero V; Miteva M (Clinical, Cosmetic and Investigational Dermatology, 2018)
Victoria Billero, Mariya MitevaDepartment of Dermatology and Cutaneous Surgery, University of Miami School of Medicine, Miami, FL, USAAbstract: Traction alopecia (TA) affects one-third of women of African descent who wear various forms of traumatic hairstyling for a prolonged period of time. The risk of TA is increased by the extent of pulling and duration of traction, as well as the use of chemical relaxation. The frequent use of tight buns or ponytails, the attachment of weaves or hair extensions, and tight braids (such as cornrows and dreadlocks) are believed to be the highest risk hairstyles. TA can also occur in the setting of religious and occupational traumatic hairstyling. In its later stages, the disease may progress into an irreversible scarring alopecia if traumatic hairstyling continues without appropriate intervention. The most common clinical presentation includes marginal alopecia and non-marginal patchy alopecia. A clue to the clinical diagnosis is the preservation of the fringe sign as opposed to its loss in frontal fibrosing alopecia (FFA). Dermoscopy can be helpful in the diagnosis and can detect the ongoing traction by the presence of hair casts. Histopathology can distinguish TA from alopecia areata, FFA, and patchy central centrifugal cicatricial alopecia. Currently, there is no cure. Therefore, it is imperative that clinicians educate high-risk populations about TA and those practices that may convey the risk of hair loss. Keywords: hair loss, alopecia, dermoscopy, trichoscopy, traction alopecia, African-American